Glioma saraf optik sebagai perluasan dari glioma cerebrii: sebuah laporan kasus - Anak Agung Surya Nirmala Dewi; Putu Yuliawati; Ni Made Laksmi Utari; Anak Agung Ayu Sukartini Djelantik; I Made Agus Kusumadjaja (Intisari Sains Medis, 2021)
Introduction: Optic Nerve Gliomas (ONG) are the most common primary Cerebral Nervous System tumor in childhood with greatest tendency for growth in the first 3-5 years of life (Huang, 2020). Most children diagnosed with ONGs have neurofibromatosis type 1 (NF-1) (Simmons,2013) with painless and slowly progressive decreace of vision. Imaging investigation with CT-scan or MRI is important to diagnose patient with ONG. The aim of this paper is to report a case of optic pathway glioma resulting rapid death of a child.Case Illustration: A 7-year-old girl complained that her eyes could not see in the past 1 year and protrusion with a white spot that is getting wider in the middle of the eye on her right eye since 3 months ago. Her left eye could not see in the past 3 weeks. She also complained about pain on her head. From ophthalmology examination visual acuity both eyes are no light perception. On her right eye we found protrusion with scleral show and lagophthalmos on her right eye, periconjunctival injection with corneal edema, deep anterior chamber and IOP 47. On the left eye we found midilated pupil with decreased reflex and the posterior segment we found optic nerve head hazy demarcated, cup-disc ratio difficult to be evaluated, good retina, decreased macular reflex and macular star (+). From right eye USG we found severe vitreous opacity. The MRI result from June 15th 2020 is suggested for optich pathway glioma dd/ pylocystic astrocytoma and suspected expand to internal auditory canal dextra. The patient was diagnosed with OD Proptosis ec retrobulbar tumor susp optic nerve glioma that expand from chiasma / cerebrii + vitreous bleeding+secondary glaucoma. OS Optic Nerve Edema ec intracranial mass. The patient was planned for OD extended enucleation join op Tumor Removal from Neuro Surgery under General Anesthesia. However, the surgery was postponed due to unstable condition and patient died from septic shock 2 months after the first arrival at the eye clinic.Conclusion: Optic Nerve Glioma are the most common primary Cerebral Nervous System tumor in childhood. This patient came with decrease of vision, protrusion on her right eye and pain with MRI finding suggested for optic nerve glioma. This patient should have done surgery but her condition was unstable. Good handling and multidisciplinary cooperation in the diagnosis and management of intraocular and intracranial masses are needed to provide a good outcome for the patient. Pendahuluan: Glioma Saraf Optik (GSO) merupakan tumor otak primer yang paling banyak terjadi pada 1 dekade kehidupan dengan kecenderungan terjadi pada usia 3-5 tahun. Anak-anak yang didiagnosa dengan GSO biasanya memiliki neurofibromatosis tipe 1 (NF-1) yang timbul secara sporadik. GSO memiliki gejala penurunan penglihatan tanpa adanya rasa nyeri yang dirasakan perlahan. Pemeriksaan penunjang dalam menegakkan diagnosis GSO bisa menggunakan CT-scan ataupun MRI. Tujuan dari makalah ini adalah untuk melaporkan sebuah kasus bagaimana cara mendiagnosa glioma saraf optic pada anak-anak.Ilustrasi kasus: Pasien perempuan, 7 tahun, datang (2 Juni 2020) dengan keluhan kedua mata tidak dapat melihat sejak 1 tahun yang lalu dan mata kanan menonjol sejak 3 bulan disertai bintik putih yang semakin melebar di bagian tengah mata. Mata kiri dikatakan tidak bisa melihat sejak 3 minggu yang lalu. Nyeri kepala sering dikeluhkan oleh pasien di seluruh kepala. Pemeriksaan oftalmologi didapatkan visus kedua mata no light perception (NLP), proptosis dengan scleral show dan lagoftalmos 2 mm pada mata kanan. Konjungtiva mata kanan didapatkan injeksi perikorna dengan edema kornea. Bilik mata depan mata kanan kesan dalam. Tekanan intraokular mata kanan 47 mmHg. Middilatasi dengan penurunan reflek pupil didapatkan pada mata kiri, lensa jernih dan pada pemeriksaan segmen posterior didapatkan papil nervus optik batas kabur, cup-disc ratio (CDR) sulit dievaluasi, retina kesan baik, reflex makula menurun dengan macular star. Hasil USG mata kanan didapatkan kesan kekeruhan vitreous berat. Pada 15 Juni 2020 pasien dilakukan MRI dengan kesan mengarah pada optic pathway glioma dd/ pylocytic astrocytoma dan suspek perluasan ke regio internal auditory canal dextra. Pasien didiagnosis dengan OD proptosis ec tumor retrobulber susp glioma saraf optik yang berasal dari chiasma / cerebri + perdarahan vitreus + glaukoma sekunder, OS Papil edema ec massa intracranial dan direncanakan OD extended enukleasi join op tumor removal oleh Bedah Saraf dengan General Anestesi. Namun, pasien belum dilakukan operasi karena keadaan pasien memburuk dan meninggal akibat syok sepsis 2 bulan pasca kedatangan pertama ke poli mata. Simpulan: Glioma saraf optik merupakan tumor yang sering ditemukan pada anak-anak. Pada pasien sudah didapatkan nyeri, penurunan tajam penglihatan dan proptosis serta gambaran MRI yang mendukung diagnose glioma saraf optic. Sebaiknya pasien dilakukan tindakan pembedahan namun keadaan umum pasien tidak memungkinkan. Penanganan yang baik dan kerjasama multidisiplin dalam penegakan diagnosis dan tatalaksana massa intraocular maupun intracranial dibutuhkan untuk memberikan luaran yang baik bagi pasien.